Cyclosporin-A Treatment in Steroid Nonresponsive Nephrotic Syndrome - IGN Wila Wirya; Taralan Tambunan; Husein Alatan (Paediatrica Indonesiana, 1994)
Fifteen patients with steroid nonresponsive nephrotic syndrome (NS) aged 4-16 years received oral cyclosporin-A (CyA) for 12 weeks. Nine of the patients were boys. Out of the 15 patients, 7 were frequent relapsers, 3 were steroid dependents, 4 were steroid resistants and one with toxic steroid. After 12 weeks of CyA treatment;, 6 patients showed complete remission, 7 showed partial remission, and 2 patients did not respond at all. Side effects observed were slight renal function impairment, gingival hyperplasia, and a hump on the breast; all disappeared gradually after stopping CyA. Patients with total remission experienced relapse 2 to 12 months after discontinuation of CyA, while patients with partial remission experienced relapse 2 weeks to 3 months after CyA was discontinued A tentative conclusion can be drawn that CyA is a good alternative in the treatment of idiopathic NS, especially in steroid dependent patients who are at risk of developing steroid toxicity. CyA represent a major advance in the treatment selected SN patients who have failed with the conventional modes of therapy.